Endoscopic ultrasonography‐guided transmural drainage of walled‐off pancreatic necrosis: Comparison between a specially designed fully covered bi‐flanged metal stent and multiple plastic stents. Issue 1 (13th September 2016) - Bapaye, Amol; Dubale, Nachiket A; Sheth, Keyur A; Bapaye, Jay; Ramesh, Jayapal; Gadhikar, Harshal; Mahajani, Sheetal; Date, Suhas; Pujari, Rajendra; Gaadhe, Ravindra
Abstract : Background and Aim: Endoscopic ultrasonography (EUS)‐guided drainage of walled‐off necrosis (WON) may be carried out by placement of multiple plastic stents (MPS) or specially designed fully covered bi‐flanged metal stents (BFMS). Comparative data on efficacy of these two stent types for WON drainage are limited. This retrospective study compares outcomes of WON drainage using BFMS and MPS. Methods: During a 10‐year period, 133 patients underwent EUS‐guided WON drainage. MPS or BFMS were placed in a WON cavity through a single puncture, and direct endoscopic necrosectomy (DEN) was carried out whenever clinically necessary. Data in the two cohorts were retrospectively compared for primary outcomes – clinical success, adverse events and mortality; and secondary outcomes – DEN requirement, mean DEN sessions, need for salvage surgery and hospital stay. Results: MPS were placed in 61 and BFMS in 72 patients. Patients undergoing BFMS drainage required fewer DEN sessions (mean 1.46 vs 2.74, P  < 0.05), had fewer adverse events (5.6% vs 36.1%, P  < 0.05), needed salvage surgery less often (2.7% vs 26.2%, P  < 0.05), and had significantly shorter hospital stay (4.1 vs 8 days, P  < 0.05) compared to those undergoing MPS drainage. There was no difference in DEN requirement ( P  = 0.217) and mortality ( P  = 0.5) in both groups. Overall clinical success with BFMS was superior to MPS (94% vs 73.7%, P  < 0.05). Conclusion: BFMS appear to be superior to MPS for EUS‐guided WON drainage in terms of clinical success, number of DEN sessions, adverse events, need for salvage surgery and hospital stay.